INCIDENCE OF PARAPHENYLENE-DIAMINE POISONING IN THREE DISTRICT HEADQUARTER HOSPITALS OF PAKISTAN - Ansari, Rizwan Zafar; Khosa, Abrar Hussain; Yadain, Syed Muhammad; Shafi, Shagufta; Haq, Anwar ul; Khalil, Zahid Hussain (Journal of Ayub Medical College Abbottabad, 2019)
Background: Paraphenylene-diamine (PPD) poisoning is an emerging problem of developing African and South Asian countries. This study was done with the objective to determine the clinical lab diagnostic accuracy of serum creatinine phosphokinase in cases initially reporting facial oedema followed by renal failure and rhabdomyolysis due to paraphenylene-diamine (PPD) poisoning. Methods: It was a cross-sectional study in which data was retrospectively collected at District Head Quarter (DHQ) Hospitals. Data was collected over a period of one year from Jan-Dec 2018. Data was collected from the patient file records. Data was analysed on SPSS version 20. Results: In the present study, 658 cases of Kala Pathar poisoning presented and treated. M: F ratio was 5:20. There were 518 (78.8%) females. Majority of the female patients were married 488 (94%). Most common clinical manifestations included marked facial oedema; dysphagia and stridor. Post complications include rhabdomyolysis and acute renal failure which developed after two to five days. Initial lab investigations within 6-8 hours after ingestion showed marked increase in TLC count, ALT and Na+ ions. There were marked elevation of serum CPK (1400 ±200 U/L) levels after 24 hours. Conclusion: PPD poisoning is more common in females of younger age group belonging to rural areas. Early diagnosis and prompt supportive treatment within 2-12 hours of ingestion can save many lives. There is no specific antidote available for this poison. Keywords: Rhabdomyolysis; Para Phenylene Diamine; Acute renal failure; Creatinine kinese, CK